Pengembangan Lembar Kerja Siswa Matematika Berbasis Pendekatan Saintifik dan Strategi Pembelajaran PQ4R Pada Materi Terkait - Eka Romiyati; Adriyan Ardi Rahman; Eddy Budiyono (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study was to produce math worksheets based on a scientific approach and PQ4R learning strategies on set material in class VII SMP and to find out whether worksheets based on scientific approaches and PQ4R learning strategies on set material for class VII SMP meet the valid, practical and effective criteria. Methodology: This type of research is development research with the ADDIE development model. This study designed worksheets, gave tests to find out student learning outcomes, and gave questionnaires to find out the results of student responses. The instruments used in this study were material and design expert assessment sheets of worksheets, teacher and student response questionnaires and observation sheets, learning achievement tests, and student response questionnaires in use trials. Main Findings: The process of developing student worksheets that have been carried out is followed by the validation stage carried out by material experts, obtaining a score of 95 in the